1960
DOI: 10.1111/j.1570-7458.1960.tb00454.x
|View full text |Cite
|
Sign up to set email alerts
|

FOOD PLANT RELATIONSHIPS OF THE DIAMOND‐BACK MOTH (PLUTELLA MACULIPENNIS (CURT.)): I. Gustation and Olfaction in Relation to Botanical Specificity of the Larva

Abstract: The exclusion of botanical species from the food plant range of the diamond‐back moth larva is determined not only by the infrequency of adequate stimulants for feeding but also by a high frequency of occurrence of feeding inhibitors. A few plant species lack feeding inhibitors but are excluded by a deficiency of feeding stimulants. Some plants are devoid of decisive feeding inhibitors and contain effective feeding stimulants but yet are excluded as host plants by the possession of toxic principles. At least o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

1974
1974
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 8 publications
(11 reference statements)
1
27
0
1
Order By: Relevance
“…This may explain why the host range of the diamondback moth is thought to be 'essentially coincident with the botanical distribution of glucosinolates' (Gupta & Thorsteinson, 1960a). We have also found that the adult diamondback moth does not discriminate between different side-chain structures of glucosinolates.…”
Section: Discussionmentioning
confidence: 58%
“…This may explain why the host range of the diamondback moth is thought to be 'essentially coincident with the botanical distribution of glucosinolates' (Gupta & Thorsteinson, 1960a). We have also found that the adult diamondback moth does not discriminate between different side-chain structures of glucosinolates.…”
Section: Discussionmentioning
confidence: 58%
“…2a, b). Glucosinolates are not an absolute requirement for food acceptance, as P. xylostella can be raised over several generations on artificial diets or P. sativum (sweet pea; Gupta and Thorsteinson, 1960), which do not contain glucosinolates.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that some standing genetic variation for the ability to feed on legumes and on other host plant species exists in DBM populations: DBM has occasionally been found on plants other than Brassicaceae, among them plants from the Fabaceae family (Robinson et al, 2010). Gupta and Thorsteinson (1960) showed that some DBM larvae were able to survive on legumes under laboratory conditions. Moreover, an unrelated C-strain responded to laboratory selection on pea to increase its survivorship to nearly 50% over six generations (Lö hr and Gathu, 2002).…”
Section: Heterogeneity In P-strainmentioning
confidence: 99%